Struktur dan Fungsi Kepemimpinan Politik - Aida Yusuf; Alencia Muryati; Citra Dwi Rahayuningsih; Nor Islamy; Surya Sukti (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
Leadership is a fundamental element in social life and political systems. In a social context, leadership is understood as the ability of an individual to influence, guide, and empower members of society in order to achieve common goals based on prevailing values and norms. Meanwhile, political leadership relates to the activities of power holders in decision-making processes and the implementation of public policies for the broader public interest. Political leadership requires not only managerial and strategic competence, but also moral integrity, as reflected in leadership concepts found in the Qur’an and Hadith. Furthermore, legitimacy is a crucial aspect of political leadership as it determines the extent to which a leader’s authority is accepted and recognized by society. Legitimacy may derive from tradition, charisma, or rational-legal foundations. In modern democratic systems, legitimacy is generally obtained through constitutional mechanisms and public support. The structure of political leadership consists of formal and informal elements that are interconnected, while its functions include decision-making, direction-setting, social integration, political communication, and the maintenance of stability. Therefore, effective leadership requires synergy between legitimacy, institutional structure, and the proper implementation of functions in order to achieve social welfare and political stability.